Understanding the Corpus of Mobile Payment Services Research: An Analysis of the Literature Using Co-Citation Analysis and Social Network Analysis - Verma, Surabhi; Chaurasia, Sushil S.; Singh, Vibhav (Journal of Information Systems and Technology Management, 2020)
Mobile Payment Services have evolved in the past 20 years, attracting the attention of international practitioners and research scholars. Although several review and analyses of literature have been conducted to examine the multiple dimensions of mobile payment services, no co-citation analysis has been conducted to examine and understand the knowledge structures involved in mobile payment services studies. Therefore in order to fill this research gap, this research article analyses the corpus of mobile payment services research published from 1997 to June 2017 using Bibliometric and Social Network Analysis (SNA) methods to develop an intellectual structure of mobile payment services research. All data source documents (406 articles and 3,424 citations) were obtained from Web of Knowledge (WoK) database. A co-citation analysis was used to analyse mobile payment services data. Factor analysis, citation and co-citation analysis, multidimensional scaling and centrality measurement are applied to the mobile payment services dataset using UCINET to identify the core influential articles in the field. This study identifies seven core clusters of mobile payment services research that centre around (1) Adoption and usage; (2) Trust, risk and security; (3) Application; (4) Scheme; (5) Protocol; (6) Architecture; (7) Mobile payment corporation. The findings of this research study provide core knowledge and directions for practitioners and researchers interested in the mobile payment services field.